Comparison of Seizure-Free Rates Between Levetiracetam and Phenytoin Administration in Seizure Patients with Brain Metastases Tumor (BM) During Period January 2023-December 2024 - Dhiandra Dwi Hapsari; Teddy Tejomukti; Ranum Anggun Nastiti (Magna Neurologica, 2025)
Background: Brain metastase tumor (BM) is the most frequently found intracranial tumor. The prevalence of seizures in BM ranges from 30%-50%. One of the treatments for seizure patients with BM is the administration of Anti-Epileptic Drugs (AED). The latest neuropharmacology now makes Levetiracetam (LEV) the first-line choice in BM cases compared to phenytoin (PHT), which was previously often used in BM cases. Objective: This study aims to compare seizure-free rates in patients with seizures on BM who received PHT or LEV treatment at Regional General Hospital Dr. Moewardi Surakarta from January 2023 – December 2024. Methods: An observational study using a cross-sectional method with a retrospective approach. Patients included were patients with BM who experienced seizures and received AEDs, either PHT 2x100 mg or LEV 2x500 mg, for a minimum duration of 6 months during the period January 2023–December 2024. Results: There were 50 research subjects with an age range of 38-67 years. The independent T-Test showed a significance value of 0.007 < value (0.05). In the group of patients given PHT, the seizure-free rate was 6.83±1.26 a (7 months), while in the LEV group, it was 9.02±0.85 b (9 months). Conclusion: A longer seizure-free rate in research subjects with LEV than PHT was found. This result is to previous research regarding the effectiveness of LEV as the leading choice in seizure patients with BM.